Six Weeks of Basketball Combined With Mathematics in Physical Education Classes Can Improve Children's Motivation for Mathematics - Wienecke, Jacob; Hauge, Jesper; Nielsen, Glen; Mouritzen, Kristian; Damsgaard, Linn (Frontiers in Psychology, 2021)
This study investigated whether 6 weeks of basketball combined with mathematics once a week in physical education lessons could improve children's motivation for mathematics. Seven hundred fifty-seven children (mean age = 10.4 years, age range: 7–12 years) were randomly selected to have either basketball combined with mathematics once a week (BM) or to have basketball sessions without mathematics (CON). Children in BM and CON motivation for classroom-based mathematics were measured using the Academic Self-Regulation Questionnaire (SRQ-A) before (T0) and after the intervention (T1). Among the BM, levels of intrinsic motivation, feelings of competence, and autonomy were measured using the Post-Experimental Intrinsic Motivation Inventory (IMI) questionnaire acutely after a basketball session combined with mathematics and immediately after a session of classroom-based mathematics. BM had significantly higher acute levels of perceived autonomy (+14.24%, p < 0.0001), competencies (+6.33%, p < 0.0001), and intrinsic motivation (+16.09%, p < 0.0001) during basketball sessions combined with mathematics compared to when having classroom-based mathematics. A significant decrease in the mean for intrinsic motivation was observed from T0 to T1 for CON (−9.38%, p < 0.001), but not for BM (−0.39%, p = 0.98). BM had a more positive development in intrinsic motivation compared to CON from T0 to T1 (p = 0.006), meaning that BM had a positive influence on children's intrinsic motivation for classroom-based mathematics. This study indicates that basketball combined with mathematics is an intrinsically motivating way to practice mathematics, which also has a positive influence on children's general intrinsic motivation for mathematics in the classroom.